Individual and combined contamination of the toxic metals in commercial cat and dog food - Jiaying Du; Kerui Zhou; Han Jiang; Shen Hu; Wei Zhang; Qiang Zheng; Guangteng Zhou; Niya Zhang (Scientific Reports)
Abstract As the long-term accumulation of toxic metals in food poses significant health risks to pets, there is a growing concern among people regarding toxic metal contamination in pet food. In order to investigate the toxic metals levels in pet food in China, we collected a total of 93 imported cat and dog food from the Chinese market produced in 2021–2022, comprising 45 cat food and 48 dog food, and determined the concentrations of lead (Pb), cadmium (Cd), chromium (Cr), mercury (Hg) and arsenic (As) in them. The concentrations of Pb, Cd and Cr were determined by flame atomic absorption spectrometry, while Hg and As were quantified by atomic fluorescence spectrometry. The most contaminated of all samples were Cr and As, which were detected in all samples, followed by Hg, which was detected in 91 samples. In cat food, Cr and As were the most prevalent toxic metals, and Cr and Hg were found in all dog food. Pb was not detected in the canned food, while both cat and dog canned foods showed relatively high contamination rates of Cr, As, and Hg. Cr, Hg and As had the highest contamination levels in dry food. Some samples exceed the limits set by Hygienical Standard for Pet Feed of China (Announcement No. 20 of 2018) regarding Pb and Cr, while other toxic metals remained within acceptable limits. Canned food, however, met all regulatory limits for toxic metals. Across all types of pet food, Cr, Hg, and As were consistently the most prevalent combined contaminants. Analysis of the acute hazard index (aHI) values showed that both cats and dogs face potential dietary exposure risks to the toxic metals investigated, with Cr posing the most significant risk, followed by Pb and As. This study underscores the extensive presence of toxic metal contamination in pet foods, posing a significant risk to pet health due to ongoing exposure to multiple toxic metals.